1985
DOI: 10.1002/jlb.37.2.209
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Activation by Cross-Linked Dextran

Abstract: Cross-linked dextran (Sephadex) has been reported as an effective inducer of peritoneal exudates resulting in a large yield of macrophages after injection into mice, and macrophages obtained in this manner have been used for a variety of studies. We examined the possibility that cross-linked dextran not only induces peritoneal exudate but functions also as a macrophage activator. Following confirmation of a markedly increased yield of macrophages in Balb/c mice injected with preswollen Sephadex G-25 beads, gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Control amino-dextran (without TO) caused an unexpected, but mild, increase in cytokine production. This is consistent with prior reports of immune stimulation by dextran in mice 17-19. Of note, the same amino-dextran preparation was used to synthesize Dex-TO, making the large reductions in cytokine production produced by Dex-TO even more noteworthy.…”
Section: Resultssupporting
confidence: 90%
“…Control amino-dextran (without TO) caused an unexpected, but mild, increase in cytokine production. This is consistent with prior reports of immune stimulation by dextran in mice 17-19. Of note, the same amino-dextran preparation was used to synthesize Dex-TO, making the large reductions in cytokine production produced by Dex-TO even more noteworthy.…”
Section: Resultssupporting
confidence: 90%
“…Recently. Blanckmeister et al showed that crosslinked dextran {1,6-a-glucan) could stimulate macrophages in vivo to become cytotoxic in vitro [5]. However, these investigators did not determine the purity of their macrophage cultures.…”
Section: Enhancement Atid Inhibition Of Curdlanmediated Cylotoxicity mentioning
confidence: 99%
“…It is therefore conceivable that the stimulatory effect of the 1.3->9-glucans is due to the particulate and rigid state of these molecules and hence other watersoluble polysaccharides when presented to the macrophages in particulate form would be as stitnulutory as the 1,3-jtf-glucans. Indeed, a recetit report suggests that particulate 1.6-a-glucan (dextran) can activate peritoneal macrophages to kill ttimour cells in vitro [5],…”
mentioning
confidence: 99%
“…This variation in experiments assessing monokine production by the aged might relate to differences in technique, especially methods to obtain macrophages. Different agents used to elicit peritoneal macrophages for study have been shown to alter macrophage function (Edelson et al, 1975;Johnston et aL, 1978;North, 1978;Ruco and Meltzer, 1978;Hopper and Geczy, 1980;Ogmundsdottir, 1980;Spitalny, 1981;Rasmussen et al, 1983;Leijh et aL, 1984;Blanckmeister and Sussdorf, 1985;Hopper, 1986;Tannenbaum et aL, 1987;Melnicoff et al, 1989;Higuchi et al, 1990;Reed and Burnham, 1991;Tomioka and Saito, 1992) and possibly monokine production (Marcinkiewicz, 1991) through mechanisms that are not yet well defined. In this study, the effects of various eliciting agents, complete Freund's adjuvant (CFA), thioglycollate (TG), or no treatment, on IL-l, IL-6, and TNF bioactivity in peritoneal macrophage supernatants from young, middle aged, and aged mice was assessed.…”
Section: Introductionmentioning
confidence: 99%